Storm blueprints : patterns for distributed real-time computation : use storm design patterns to perform distributed, real-time big data processing, and analytics for real-world use cases /: patterns for distributed real-time computation : use storm design patterns to perform distributed, real-time big data processing, and analytics for real-world use cases. (2014) - Unknown
No abstract available